The ethos of non-existence - Santos, Girlandia Gesteira; Santos, Yuri Andrei Batista; Torga, Vânia Lúcia Menezes (Linha D'Água, 2024)
In the line of dialogue between discourse studies and argumentation studies, we analyze the construction of ethos in the paratext of the book Recordações da minha inexistência - memórias (Recollections of my non-existence – memoir) by Rebecca Solnit (2021). In view of a writing that traces a counter-hegemonic discourse in the underlying social context in the argumentative dimension, an important point to observe is how the discursive project of this autobiographical writing articulates itself in the construction of the narrative ethos of the author-narrator-personage. To this end, we will analyse the paratextual elements of the work. We consider that the ethos of female non-existence in this work occurs in linguistic and extralinguistic conditions that compose a self which resonates in the collectivity. From the analyses of the paratext of the work, we highlight how the construction of the discursive ethos of the author-narrator-character reflects and refracts the constitutive social conflicts of female self-representation in contemporaneity, in an aporetic way marking the female self-reference through the logic of a non-place.